INVESTOR REACTION TO STOCK SPLIT IN MANADO - Rumapea, Valentino (Universitas Sam Ratulangi, 2013)
Market might react in several different ways in facing the stock split action. Some might positively react and increasing the number of transaction, some might do the opposite, or some might not care at all. It is all depend on the investor behavior and perception of the stock split. The changes could be seen in the number of stock volume transaction post-split compared to the pre-split, but the reason behind those actions left people to only guessing. The only way to know about how and why investors react to stock split is to ask them directly. The objective of research is to analyze the investors’ reaction to stock split. Theories supporting research are investment and stock split. The population of research is all stock investors in Manado with 7 respondents using purposive sampling method. Results are (1) investors in Manado are not attracted to stock split; (2) the investors are not attracted to the stock split announcement with three reasons namely: less exposure to the market because of the long-term investment, the rule of analyses, and the amount of funds. It is concluded that investors in Manado are showing an under-reaction to stock split. Keywords: stock split, investor reaction